Zweckmässigkeit ohne Zweck: ideias kantianas presentes na estética de Goethe - Guidotti, Mirella [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis investigates the affinities between the ideas of Kant’s Critique of Judgment and Goethe´s aesthetic thought, by dealing with aspects in Goethe´s texts from 1786 on, when Goethe made his renowned journey to Italy, a landmark in the construction of his aesthetics. Through the concept of purposiveness without a purpose [Zweckmässigkeit ohne Zweck], one of the key terms of Kant´s Third Critique, it is intended to explore the aesthetic concept, which states that the artwork ist not reducible to an explanation or deduction in a science of beauty. The value of art should lie in itself; the art has an intrinsic value, not projected for any purpose than itselt. Through the notion of purposiveness without a purpose one should undestand the independency of the judgment of an art object in regard to other spheres, whether moral, historical or philosophical, not instrumentalizing thereby the literary text to any outside purposes, since no external speech is able to translate the truth of the poetic text. In this sense, the term relates the moment of rupture with the normative aesthetic tradition prevalent in previous centuries, as the sphere of art is to both, Goethe and Kant, an area that remains inexpressible. For Goethe, art is also a domain that creates its own world, its own truths, and in this sense should be judged only from its intrinsic rules. The idea of the untranslatability of the art manifests, though in his own way, also in Goethe. From the 90´s on, this idea reaches considerable importance to the poet and even the mature Goethe appeals to Kant and specially to the idea of the autonomy of art. Here, the last Goethe´s novel Die Wahlverwandtschaften is analyzed according to the theoretical premises discussed in the first part of this thesis: the novel´s critical analysis intends thereby to incorporate the concept of the art as an untranslatable domain. We argue that this way of critical analysis is suitable for the ...

A tese investiga as afinidades de ideias entre a Crítica da Faculdade do Juízo de Kant, e o pensamento estético de Goethe, abordando os elementos presentes nos textos que o escritor produziu sobretudo a partir de 1786, ano em que realiza a famosa viagem à Itália e espécie de marco zero na construção de sua estética. Pelo conceito kantiano de finalidade sem fim [Zweckmässigkeit ohne Zweck], um dos termos decisivos de sua Terceira Crítica, pretende-se apreciar a concepção segundo a qual a obra de arte não seria redutível a uma explicação ou dedução em uma ciência do Belo, detentora que é de valor intrínseco, avessa a qualquer finalidade que não seja ela própria. Por finalidade sem fim, entende-se, pois, a independência de julgamento do objeto de bela arte face a outras instâncias, sejam elas morais, históricas ou filosóficas, não cabendo instrumentalizá-la no sentido de qualquer finalidade que seja exterior a ela, uma vez que nenhum discurso exterior é capaz de traduzir a verdade do texto poético. Nesse sentido, a formulação representa uma ruptura com a tradição estética predominante em séculos anteriores. A arte, para Goethe como para Kant, constitui, no limite, um campo inexprimível. Em Goethe, a arte produz seu próprio mundo, suas próprias verdades, e por isso mesmo não deve ser julgada senão a partir de suas leis intrínsecas, conceito que abriga também, ainda que com traje específico, a ideia de sua intraduzibilidade. Desde os anos 1990, essa ideia vem adquirindo especial importância para os estudos de Goethe, valendo salientar que mesmo o Goethe maduro recorre a Kant e, em especial, à ideia da autonomia da arte. Na última parte deste trabalho, tendo em consideração os pressupostos teóricos acima arrolados, procede-se à análise crítica de seu último romance, As afinidades eletivas [Die Wahlverwandtschaften], com uma metodologia que se mostra apropriada para a obra em apreço ...
Keywords: Kant, Immanuel 1724-1804 Crítica e interpretação; Goethe, Johann Wolfgang von 1749-1832 Crítica e interpretação; Literatura - História e critica - Teoria, etc; Literatura - Estetica; Literature Aesthetics